Social adaptation of children in married women of Central Asia in South Korea in 2000 - Yem, N. (Journal of Oriental Studies, 2016)
This article examines the difficulties of social adaptation in international marriage. The author updates the intolerantnoe attitude of the host society with respect to children born in Korean-Asian marriage in South Korea.